Transgenic mouse models of prion diseases - Telling, Glenn (Henry Stewart Talks, 2008)
Prions represent a new biological paradigm of protein-mediated information transfer, Prions are the cause of fatal, transmissible neurodegenerative diseases, often referred to as transmissible spongiform encephalopathies (TSEs), Many unresolved issues remain including the exact molecular nature of the prion, the detailed mechanism of prion propagation, and the mechanism by which prion diseases can be both genetic and infectious, The factors governing the transmission of prions between species remain unclear, in particular the means by which prion strains and PrP primary structure interact to affect inter-species prion transmission, Dramatic advances in our understanding of prions have occurred because of their transmissibility to experimental animals and the development of transgenic (Tg) mouse models has done much to further our understanding about various aspects of prion biology